2019
DOI: 10.1371/journal.pone.0226363
|View full text |Cite
|
Sign up to set email alerts
|

Free thiol groups on poly(aspartamide) based hydrogels facilitate tooth-derived progenitor cell proliferation and differentiation

Abstract: Cell-based tissue reconstruction is an important field of regenerative medicine. Stem and progenitor cells derived from tooth-associated tissues have strong regeneration potential. However, their in vivo application requires the development of novel scaffolds that will provide a suitable three-dimensional (3D) environment allowing not only the survival of the cells but eliciting their proliferation and differentiation. Our aim was to study the viability and differentiation capacity of periodontal ligament cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 55 publications
2
16
1
Order By: Relevance
“…This observation suggests that a great amount of PDLCs could adhere to the DA-free gels, but on this gel type, they were not able to proliferate. Previous studies on PASP hydrogels are also in line with our observations, and it has been described that these gels provide a suitable surface for cell adhesion and proliferation of PDLCs [15] and MG-63 osteosarcoma cells [8]. However, the viability of PDLCs did not change notably on DAcontaining gels during the 14-day-long experiment.…”
Section: Cell Viability and Morphology On Different Pasp-da Hydrogelssupporting
confidence: 92%
See 1 more Smart Citation
“…This observation suggests that a great amount of PDLCs could adhere to the DA-free gels, but on this gel type, they were not able to proliferate. Previous studies on PASP hydrogels are also in line with our observations, and it has been described that these gels provide a suitable surface for cell adhesion and proliferation of PDLCs [15] and MG-63 osteosarcoma cells [8]. However, the viability of PDLCs did not change notably on DAcontaining gels during the 14-day-long experiment.…”
Section: Cell Viability and Morphology On Different Pasp-da Hydrogelssupporting
confidence: 92%
“…Currently, there are only a few types of synthetic poly(amino acids) available, such as polylysine or poly(aspartic acid) (PASP) that can be suitable for this purpose [ 10 , 11 ]. In our previous studies, the chemical constitution and the physical properties of PASP-based hydrogels have been comprehensively investigated [ 12 , 13 , 14 ] and successfully tailored for applications as a scaffold [ 8 , 15 ]. We have demonstrated that thiol groups in the PASP hydrogels facilitate cell adhesion and proliferation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, there is a wide range of possible reconstructive methods that can be applied to rebuild damaged tissues such as tissue engineering using stem cells (9)(10)(11), gene therapy (12,13) and artificial biocompatible scaffolds (14,15), but their use has been not well-established in routine clinical settings. Among the non-surgical regenerative and reconstructive procedures, hyaluronic acid (HA)-based dermal filling is one of the most frequently used treatments (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel research we work on the development of scaffolds that allow not only the survival and proliferation of the ectomesenchyme-derived cells, both in vitro and in vivo, but also elicit their differentiation [64][65][66][67][68]. By chemical modification of biocompatible and biodegradable poly(aspartamide) (PASP)-based hydrogels, and parallel studies on their biocompatibility, biodegradability and regenerative potential, we are attempting to develop novel scaffolds that are clinically applicable [64][65][66][67][68]. We expect that in the near future these separate lines of research, on microcarriers and scaffolds, will meet through the development of biomaterials that can serve both for cell expansion and tissue regeneration.…”
Section: Discussionmentioning
confidence: 99%